DELIK AGAMA DALAM PERSPEKTIF HUKUM PIDANA DAN KAITANNYA DENGAN HAM - Maria Silvya E. Wangga (Jurnal ADIL, 2019)
his research explains Article 156a of the Indonesian Code Penal aboutblasphemy. This Article can only be apllied the implementation of Articles 1,2,and3 of the Act number 1/1965 on Protection, Abuse and or Blasphemy. Those articlesregulate the requirements of the settlement of blasphemy. Those requirementsconsist of 1) letter from the minister of religion, the attorney general and theminister internal affairs; 2) The President of the Republic Indonesia will state thatwhether and religious organization will be prohibited and 3) when the prohibitedorganization will continue has activites than at will be sunction by 5 years ofimprison. In this paper, the writer will also explain the implementation of Article156a of Indonesian Code Penal and Article 1,2,and 3 of the Act number 1/1965 onProtection, Abuse and or Blasphemy is in accordance with principles of humanrights